The effect of calcium lignosulfonate on ettringite formation in cement paste. (May 2018) - Colombo, A.; Geiker, M.; Justnes, H.; Lauten, R.A.; De Weerdt, K.
Abstract: The effect of a softwood calcium lignosulfonate, LSs, on the ettringite formed in cement paste was investigated. Two Portland cements, mainly differing in surface area and C3 A content, were used. The effect of LSs addition time was studied, by adding either the LSs immediately with the mixing water or after 10 min of hydration. After 30 min of hydration of both cement pastes, the immediate addition of LSs caused the formation of numerous small ettringite crystals. The ettringite crystals had similar shape in pastes with and without LSs addition: cubic or cuboidal shape with length between 0.1 and 0.4 μm. These small particles caused an increase in surface area, which in turn increased the LSs adsorption by the cement paste. This could potentially lead to incompatibility issues between cement and plasticizer.